Pattern of Infecting Organisms and Antibiotic Sensitivity in Compound Fractures: The value of pre-debridement culture - Khanal, Krishna Raj; Pra, Rabindra Lal; Pandey, Bimal Kumar; Manandhar, Rajiv Raj; Regmi, A; Khanal, H (Nepal Orthopaedic Association Journal, 2021)
Background: Antibiotics along with wound care is the mainstay of treatment for compound fractures to prevent infection. Despite recommended guidelines the surgeons continue to modify the antibiotics considering recommendations inadequate. Knowledge of the flora of a region can guide the antibiotic therapy. Evidence is divided regarding the role of pre debridement culture in predicting the final infection. This study is intended to find the role of initial culture and document the bacteriology of these compound fracture wounds. Method: Ninety seven patients with compound fractures presenting to a Kathmandu Medical College Teaching Hospital between June 2020 and March 2021 were included in the study. Wound swab cultures were sent at initial presentation. Standard treatment with antibiotics and wound care was instituted. At 48 hours of debridement, a repeat culture was sent. Predictiveness of pre-debridement culture for post debridement culture was analyzed. Result: Twenty-six patients had initial contamination out of which 5 patients developed subsequent infection. 12 cultures yielded organism in repeat culture. The initial culture predicted the outcome of repeat culture (McNemar, p=0.013). The most common organism in predebridement and postdebridement cultures was Staphylococcus aureus (42.3%) and Acinetobacter baumanii (41.67%) respectively.Aminoglycosides (93.3%) and cephalosporins (90.9%) had the highest overall sensitivity. For Gram negative organisms, maximum sensitivity was noted with Aminoglycosides (90%). No antibiotic resistance was noted for Gram positive organisms. Conclusion: Pre debridement culture can predict the occurrence of later infection in compound fracture though organisms tend to change over time. Commonly used antibiotics have good sensitivity.